Methodological aspects of statistical analysis in ophthalmology - A. S. Sorokin; S. Yu. Petrov; N. V. Zvezdina; M. A. Golovanova (Российский офтальмологический журнал, 2023)
Statistics can be used to evaluate the prevalence of diseases, differences between patient groups, links between test results, compare the effectiveness of different types of treatment, test the hypothesis and model the interdependencies between variables. In medical universities, preference is given to special medical disciplines. Yet, a skilled medical specialist should have an adequate understanding of statistical data analysis. Purpose: to systematize and demonstrate statistical analysis techniques that could be useful for an ophthalmologist. Results. The major methodological aspects of statistical analysis in ophthalmology are considered. An overview of statistical techniques and an algorithm of choosing such techniques is given. Descriptive statistics and features of in-depth statistical analysis used in ophthalmological research are presented. Examples of scientific work using these methods are listed. Conclusion. The basics of statistical analysis expand the scope of instruments that ophthalmologists have at their disposal. The paper provides links to open sources in which statistical techniques and results achieved therewith are presented. These links increase the ophthalmologist’s awareness of the instruments considered.